Sequential manual manipulation technique of closed reduction to retrieve a bent femoral intramedullary nail: a case report - Thami, Tarkik; Bhayana, Himanshu; Bindal, Shikhar; Srivastava, Akshat; Bansal, Arjit; Kumar, Deepak (International Journal of Research in Orthopaedics, 2024)
A bent intramedullary nail in femur can be extremely difficult to extract when a patient presents after a secondary episode of trauma following the original episode for which nailing was done. These bent nails require utmost precision while extracting them, to prevent injury to the surrounding soft tissues and neurovascular bundle of the limb. We encountered a particularly rare case of a bent Kuntscher nail who presented to us nearly 20 years (post his primary surgery in 2001) after sustaining a secondary trauma. There was a 29-degree bend in the antero-posterior view and a 106-degree procurvatum bend in the k nail on the lateral view. We followed a technique of sequential manual manipulation under radiographic guidance to correct the acute bend of the nail, taking care not to create any additional fractures. Following nail extraction, the fracture was fixed with an interlocking nail and went on to unite uneventfully. At 3-year follow up, patient was walking pain free and exhibited a good knee range of motion.